DEVELOPING MULTIMEDIA GAMIFICATION USING GENIALLY APPLICATION FOR TEACHING IRREGULAR PAST TENSE VERBS FOR JUNIOR HIGH SCHOOL STUDENTS - Rilla Inayah Putri Putri; Eliwarti; Fangiana Safitri Diah (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2026)
The learning process plays an important role in achieving educational goals, including in English language learning. In the modern digital era, learning media selection, such as multimedia, has become an important supporting aspect of English learning. Gamification is one method for delivering content, and one platform that can be used is Genially. Based on preliminary research conducted at SMP Negeri Madani Pekanbaru, it was found that the irregular past tense verb is a rather difficult topic, and the subject teacher has never used technological media, while the students enjoy learning through it. The objectives of the research are to find out the process, the validity, and the practicality of the developed media. The research was conducted using a research and development method with the Plomp Model up to 4 phases, including preliminary research, design, realization, test, evaluation, and revision. The developed media gained a very valid and very practical category, with scores of 95,24% in media evaluation, 90,91% in material evaluation, and 100% in practicality assessment. The assessment indicated that the developed media aligns with previous studies, particularly regarding gamification components and their benefits, including increased student interest and motivation, support for learning and teaching, and enhanced critical thinking and problem-solving skills.